São Paulo: visibilities of experienced and mediatized life practices on Avenida Paulista - Chen, Luciana; Barreto Bogo, Marc; Vidal Barcelos, Maria Claudia (E|C, 2021)
Avenida Paulista is one of the main financial and tourist landmarks in the city of São Paulo and occupying it is a strategy to generate visibility for the social and cultural activities that take place there. We have observed that, even during the Covid-19 pandemic, Paulista continued to be a highly mediatized place, either as a reference point to show the empty space of the city resulting from social distancing measures or as a stage for the agitated popular demonstrations that once again occupy the avenue. In this article, we will study the life practices observed in Paulista during the pandemic period, with a central issue being the visibility processes of the experienced and mediatized Paulista. Questioning how interaction and meaning regimes occur in the media and social networks and based on Eric Landowski’s sociosemiotics, we aim to understand the ways in which this public space is configured and lived, both in loco and digitalized and mediatized.